Benefits and difficulties of Electronic Government Procurement (e- GP); an analysis of Local Government Engineering Department (LGED), Thakurgaon - Prodhan, Md. Manjur Alam (BRAC Univeristy, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.